Preparation of Quality Upgraded Tuna Mas and Mas-based Diversified Convenience products - M.K., Mukundan; K.P., Antony; V., Muraleedharan (Fishery Technology, 2025)
Method of preparation of quality upgraded 'mas', the traditional smoked-dried tuna product of Lakshadweep is reported. Methods are also described for the preparation of diversified convenience products from the quality-upgraded tuna mas, viz., mas fingers, mas granules and mas soup powder and ready-to-serve items like mas chutney powder and mas pickles. Mackerel tuna (Euthynnus afinis), abundantly available on the Kerala coast, was used for the studies. Brining, smoking and drying of the fish were carried out at controlled conditions. Exposing the tuna mas to a: High-Temperature-Short-Time (HTST) thermal treatment assured stability against insects during storage. All the products showed high sensory quality. Packed in low density polyethylene-polyester laminate pouches the products showed good storage stability at ambient condition.